Works for Organ 1-3 - Linjama, Jouko 1934-2022; Lehtola, Jan (Finland Jubal, 2004)
The sound of the magnificent 1967 Marcussen organ of Helsinki Cathedral is opened up superbly by Jouko Linjamas Toccata in D, op. 63 (1985) found on Volume 1, in this three volume, three CD set devoted to the composers confident and compelling writings for organ. The composer is well served by young organist Jan Lehtola, who explores the vivid contrasts that characterise much of Linjamas works with true bearing. The contemporary nature of the works is nothing to run away from, indeed, Lehtolas distinct performances invite the listener to hear and discover the kaleidoscopic colours of the instrument, battened down by the individual yet approachable style of Linjama. The Helsinki recital on the first disc contains six imposing works both secular and sacred in theme where Linjamas penchant for baroque forms such as the Prelude, Fugue, Toccata and Partita, in his secular writing, are compounded by works based upon b-a-c-h.The Intrada per organo pleno, op.11 (1969) on the second disc is captured upon the Dutch and North German organ builders Kangasalan Urkurakentamos 1987 Choir Organ found at the Kallio Church. This is splendid stuff for the pleno before more brittle sounds are explored within the five sections of Piae Cantiones per organo piccolo, op.33 (1976), while Linjamas Toccatina, danza e contradanza per organo piccola op. 50b (1981) bounces along with sounds akin to fast dripping icicles.The atmospheric Echo 1 for oboe and organ (1981) is a rich play upon sounds, where Linjama juxtaposes these two different wind instruments to investigate their similarities and differences. This is done with great effect between oboist Janne Vilen and organist Lehtola upon the main organ found in Kallio Church built in 1995 by the Swedish firm Åkerman & Lund, modelled on the French Romantic tradition with its mechanical note and stop action. Four further works equip the listener with the capabilities of this organ, finely executed by Lehtola.The final disc in this triumvirate recording is performed on the organ of the Church of the Cross in Lahti, Finland, featuring Shadows in the façade of the organ in the Church of Cross in Lahti, op 87 (1991) for organ duet. Jan Lehtola is joined by Makku Makinen in a clever work set in three movements full of fascinating contrasts, conveyed by the marvellous sounds made upon Viekko Virtanens 1979 instrument with a façade, reflected upon in the above work, designed by Alvar Aalto.
Keywords: Helsingin tuomiokirkko (Helsinki, Finland); Kallion kirkko (Helsinki, Finland); Ristinkirkko (Helsinki, Finland); 20th Century (1901-2000); Organ music; Avant-garde; Finland